Use of ICTs and the economic performance of SMEs in East Africa - Shyamal K. Chowdhury; Susanne Wolf (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper assesses the use of information and communication technologies (ICTs) and their impact on the economic performance of small- and medium-scale enterprises (SMEs) of three East African countries: Kenya, Tanzania and Uganda. Findings of the paper suggest that the diffusion of ICT among East African SMEs is both industry and country specific. The empirical findings suggest that investment in ICT has a negative impact on labour productivity and a positive impact on general market expansion. However, such investment does not have any significant impact on enterprises' return, nor does it determine enterprises exporter (non-exporter) status.
Keywords: F35; H59; H87; 330; information and communication technology; small and medium enterprises; firm performance; market expansion; East Africa; Klein- und Mittelunternehmen; Informationstechnik; Ostafrika